TINJAUAN YURIDIS TERHADAP STATUS HUKUM DAN PERLINDUNGAN HUKUM DARI PEKERJA KONTRAK NON PEGAWAI NEGERI SIPIL (PEKERJA HONORER) BERDASARKAN UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN - Antonius Ferry Bastian; Ariawan Gunadi (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2020)
After the enactment of the ASN Law causes uncertainty and there is no certainty the status of honorary staff, because the ASN Law only mentions 2 (two) categories as in Article 6, which consists of civil servants and PPPK. This has an impact on the position of Honorary Workers in the staffing system in the ASN Law becomes unclear because in the ASN Law. Article 6 discusses that "ASN employees consist of civil servants and PPPK" based on Honorary Workers who are not currently PPPKs. Based on this background, the following problems were formulated: What is the legal status and legal protection of temporary workers not included in civil servants under the Ministry of Energy and Mineral Resources? The research method used in this thesis testing proposal is a normative legal research method. In theory, honorary staff have been eliminated or eliminated by related regulations such as the ASN Law. However, it cannot be denied that the honorary workforce is still valid and still exists within government agencies, one of which is the Ministry of Energy and Mineral Resources. The legal status only uses the term, which can be seen in the law can be prepared with freelance workers who are not approved for its sustainability. Legal protection given by the government to honorary staff is a difference, if previously the government was still half-measures in providing protection for issues of granting and protecting work rights for employees not being fulfilled full, given in this provision the position of honorary workforce is eliminated and changed to PPPK.